Conference – 2015 Equation (5)

j i t + n ¯ j i t = β N i t + ε i t MathType@MTEF@5@5@+= feaagKart1ev2aaatCvAUfeBSjuyZL2yd9gzLbvyNv2CaerbuLwBLn hiov2DGi1BTfMBaeXatLxBI9gBaerbd9wDYLwzYbItLDharqqtubsr 4rNCHbGeaGqiVu0Je9sqqrpepC0xbbL8F4rqqrFfpeea0xe9Lq=Jc9 vqaqpepm0xbba9pwe9Q8fs0=yqaqpepae9pg0FirpepeKkFr0xfr=x fr=xb9adbaqaaeGaciGaaiaabeqaamaabaabaaGcbaWaa0aaaeaaca WGQbWaaSbaaSqaaiaadMgacaWG0bGaey4kaSIaamOBaaqabaaaaOGa eyOeI0IaamOAamaaBaaaleaacaWGPbGaamiDaaqabaGccqGH9aqpcq aHYoGycaWGobWaaSbaaSqaaiaadMgacaWG0baabeaakiabgUcaRiab ew7aLnaaBaaaleaacaWGPbGaamiDaaqabaaaaa@4914@